KONSERVASI LAHAN MELALUI PENERAPAN TEKNOLOGI BUDIDAYA LORONG (ALLEY CROPPING) DI DAERAH TRANSMIGRASI KURO TIDUR, BENGKULU - Kasiran Kasiran (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
The research of land productivity through the application of alley cropping has been carried out in transmigration area Kuro Tidur, Bengkulu. The research was done continously within three planting seasons, from 1997 to 1998. The results of the research showed that Flemengia congesta as a fence crop or hedgerows was beneficial. The returning of organic matter from prunning of the hedgerows into the soil can conserve the soil through improvement of nutrients availability, increasing pH, decreasing availability of aluminium (Al) by chelate formation. The effect of dolomit 2,5 ton/ha and organic matter 5,0 ton/ha will increase soy beans production 28,9 % and increase corn production 33,1 %. The effect of dolomit 2,5 ton/ha and organic matter 10,0 ton/ha will increase soy beans production 38,6 % and increase corn production 54,9 %.